An Update Review of Approaches to Multiple Action-Based Antibacterials - John B. Bremner (MDPI AG, 2023)
Many approaches are being pursued to address the major global health challenge posed by the increasing resistance of pathogenic bacteria to antibacterial agents. One of the promising approaches being investigated includes the design and development of multiple action-based small-molecule antibacterials. Aspects of this broad area have been reviewed previously, and recent developments are addressed in this update review covering the literature mainly over the past three years. Considerations encompassing drug combinations, single-molecule hybrids and prodrugs are summarised in regard to the intentional design and development of multiple-action agents with a focus on potential triple or greater activities in bacteria. The hope for such single agents or combinations of single agents is that resistance development will be significantly hindered, and they may be useful in tackling bacterial disease caused by both resistant and non-resistant bacteria.